Effects of delayed time‐out on problem behavior of preschool children. Issue 4 (29th September 2019) - Slocum, Sarah K.; Vollmer, Timothy R.; Donaldson, Jeanne M.
Abstract : Time‐out is a common negative punishment procedure in home and school settings. Although prior studies have shown time‐out is effective, more research is needed on its effects when implementation is imperfect. We evaluated delays to time‐out with 4 preschool children who engaged in some combination of aggression, property destruction, and rule breaking. Target behavior decreased for all subjects exposed to delayed time‐out, with 3 of 4 subjects displaying low levels of target behavior even when time‐out was delayed by 90‐120 s. These data suggest delayed time‐out might be effective in situations in which a caregiver or teacher cannot implement time‐out immediately.